A review of SaiLuoTong (MLC-SLT) development in vascular cognitive impairment and dementia - Ampil, Encarnita Raya; Ong, Paulus Anam; Krespi, Yakup; Yang, Yuan-Han (Frontiers in Pharmacology, 2024)
The dementia epidemic, attributed to aging populations, represents a growing socio-economic burden. It is estimated that in 2019 about 55 million people worldwide were living with dementia. With many possible causes of dementia and the possibility of mixed dementia combining Alzheimer’s disease (AD) and vascular dementia the question is whether diagnostic uncertainty exists or whether diagnostic constructs based on single etiologies are incorrect. Vascular Cognitive Impairment and Dementia (VCID) designates the extent of cognitive dysfunctions from the most benign state to that of dementia, of vascular origin. We reviewed epidemiological, pathophysiological and clinical data on VCID with a focus on VaD, as well as key data on the development of a new therapeutic solution, SaiLuoTong (MLC-SLT). From documentary research executed on different web sources (PubMed, Clintrials.gov, Z-library and Google), our initial selection for the short review of VCID and VaD was based on keywords contained in each paragraph subtitles of this article with exclusion of publications in a language other than English or published before 2010. For the review of SaiLuoTong development, there was just the language exclusion criterion. Sorted by relevance and publication date, 47 references were selected from 140 shortlisted for review. With new evidence-based classification systems, vascular cognitive impairment was proposed as umbrella term covering all forms of cognitive deficits related to vascular causes. The scope of application expanded with the VCID which includes VaD and mixed pathologies. No drugs are approved for the treatment of VaD by major Western regulatory agencies, while some traditional Chinese medicines are registered in China. VCID treatment should have a dual focus: managing the underlying cerebrovascular disease and dementia symptoms. This is the objective set for the development of the MLC-SLT, the essential data of which are reviewed in detail. To strengthen VCID and VaD research, consensus groups should attempt to consolidate scattered local research initiatives into coordinated international programs. In two VaD clinical trials, MLC-SLT improved cognitive symptoms and activities of daily living, with good safety and potential disease-modifying effect. In a placebo-controlled study in 325 patients with mild to moderate VaD and randomized according to a delayed-start design, MLC-SLT demonstrated significant improvement in memory tests and performance in executive function tasks, expanding its place in the management of VCID. At week 26, changes in VADAS-cog scores (SD) from baseline were 23.25 (0.45) for MLC-SLT 180 mg bid), 23.05 (0.45) for MLC-SLT 120 mg bid (both p < 0.0001), and 20.57 (0.45) for placebo (p = 0.15). At week 52, differences between both groups MLC-SLT and placebo were 2.67 and 2.48, respectively (p < 0.0001), without significant difference between MLC-SLT groups.